Post Job Creation Law Land Registration: Opportunity or Threat - Sariyah, Sariyah; Luthfia, Chaula; Falah, Nabilah (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2025)
Land registration after the enactment of the Job Creation Law provides a great opportunity to accelerate and simplify the land registration process through digitalisation and the Complete Systematic Land Registration (PTSL) program. However, the implementation of this system is faced with challenges, especially in terms of socialisation to the community and access to technology. This service aims to assess the effect of legal counselling conducted in Sindangsari Village, Serang Regency, on the community's understanding of land registration procedures after the Job Creation Law. The method used in this activity is legal counselling delivered by Civil Law lecturers at the Faculty of Law, Sultan Ageng Tirtayasa University. The results of this service activity show that the legal counselling carried out has a positive impact, with increased public understanding of land registration procedures, the importance of legal land ownership, and how to access land registration electronically. Although there are still challenges related to access to technology and limited resources, the Sindangsari Village community is now better prepared to face the increasingly digitalised land registration process. This counselling contributes to strengthening community legal awareness and reducing the potential for future land disputes. Therefore, this community service activity is an important model in improving community understanding of changes in land regulations, especially related to the Job Creation Law.